Theoretical and practical aspects of pedagogy and psychology - Emelianova I. E., Mangova O. B., Vlasicheva V. V., Glotova G. A., Fedotov E. D., Liakhova E. G., Glagolev A. B., Dushina I. V., Sidorova L. V., Salankova S. E., Serkova E. I., Mueva A. V., Akhmetzianova E. I., Akhtarieva R. F., Shapirova R. R., Sofronova S. A., Vasileva I. S., Shvaikina N. S., Zaluzhnaia M. V., Krutova I. A., Fisenko M. A., Matveichik T. V., Smyslova G. A., Usheva T. F., Kozhevnikova V. V., Soboleva T. N., Kazakova T. A., Pozdnyakov A. N., Burukina O. A. (Theoretical and practical aspects of pedagogy and psychology, 2023)
the chapter describes ways to form research skills and create students' cognitive interest in the study of physics. The possibilities of using home-made equipment in physics for the organization of research activities are revealed. Examples of home-made devices used to study mechanical, light and electrical phenomena are given. Devices mounted from the simplest available materials are described, which allow organizing research on the study of physical phenomena, establishing scientific facts and discovering physical laws.
Keywords: познавательный интерес; исследовательские умения; research skills; физический эксперимент; physical experiment; cognitive interest; планирование физических исследований; самодельные приборы; домашние опыты; planning of physical research; self-made devices; home experiments